The use of local building materials for the construction of farm structures in western Nigeria (1997)
A Survey of the pattern of usage of building materials in the small - to - medium farms in Western Nigeria was undertaken. Wood was the commonest construction material in use, followed by earth products and natural fibers. Decay and weathering of natural fibers including timber; arid the erosion of earth products were the major problems experienced with their uses. Treatment of the natural products before use was found wanting. Adequate seasoning and preservative treatment of natural fibers’ and earth stabilization are recommended for durability. Cost is a vital consideration in the choice of construction materials for farm structures. The choice of local materials goes some way to reduce cost. Numerous improvements on performances of some local materials have been devised in the Research Institutes. There is a need for effective extension linkage between the research institutions and the farmers.